After-care, resettlement and social inclusion: The role of probation - Canton, Rob (Probation journal, 2022)
The priority of public protection has moved probation away from its historical concerns with providing after-care, now emphasising risk management as well as the continuation of the sentence in the community. Yet people released from prison notoriously face many difficulties in accessing the social resources they need for desistance and meet with mistrust associated with their criminal records. This paper looks at the responsibilities of the Probation Service in their supervision of people leaving prison, considering the role of probation in promoting social inclusion and supporting desistance.